LABORATORY MODEL TEST ON OF IMPROVED SOIL USING LIME-COLUMN - S.P.R. Wardani, Agus Setyo Muntohar (World Scientific Publishing, 2011)
This lime-column technique has been applied successfully in recent years to improve the physical and mechanical properties of the soils. This technique would increase soil bearing capacity and reduces soil settlement owing to improving of soil strength and stiffness. This paper presents the preliminary results of the small laboratory model test of lime-column technique on soft clay soil to investigate load-settlement characteristic in laboratory. The lime-column was designed as single column with 50 mm in diameter (D), and the depth was 100 mm. The laboratory tests carried out was one dimensional consolidation and small plate loading test. The test results show that before installation of the limecolumn, based on the load-settlement curve, the mode of failure was likely defined as general shear failure. The bearing capacity of the soft soil increased from 0.23 kN to 5.2 kN, it was about more than 20 times increasing, after the lime-column was installed. Whole results indicated that lime-column technique is a valuable method to enhance soil bearing capacity and reduce soil settlement.